Robotics Education and its Role in Enhancing Academic Persistence and Achievement in the Triângulo Mineiro Region - Silva, Aline Fernanda Furtado; Rios, Artur de Almeida; Lima, Danielli Araújo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This article investigates the impacts of higher education students' participation in robotics projects on their academic retention and success. Drawing on the analysis of experiences and project proposals developed in the Triangulo Mineiro region of Brazil, the study discusses how educational robotics can enhance student engagement, motivation, and the development of essential skills, thereby contributing to reduced dropout rates and improved academic performance. The distinctions between educational and pedagogical robotics, as well as the historical context of their application in Brazil, are examined. Recent experiences employing machine learning and data visualization to assess the impacts of robotics initiatives-including those aimed at increasing female participation-underscore the relevance and the need for more in-depth analyses. Although direct statistical data to quantify causal effects remain limited in publicly available databases for this specific region, qualitative evidence and practical examples based on local initiatives indicate a significant positive impact. The study highlights the importance of such initiatives for the comprehensive education of students in engineering and technology programs.